The Effect Of Content Marketing, Product Quality, And Service Quality On Purchase Decisions At Richeese Factory - Kesia Manalu; Rifky Budi Setiawan; Annisa Sanny (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of Content Marketing, Product Quality, and Service Quality on consumer purchasing decisions at Richeese Factory Adam Malik Branch, Medan. This study uses a quantitative approach with a causal research type. The research sample consisted of 96 respondents determined using the Cochran formula with a purposive sampling technique. Data collection was carried out through a questionnaire, while data analysis used multiple linear regression assisted by the SPSS 22 program. These findings show that partially Content Marketing has a positive and significant impact on purchasing decisions through a regression coefficient of 0.270 and a significance value of 0.006 (<0.05). Product Quality has a regression coefficient of 0.056 with a significance value of 0.530 (>0.05), which indicates that this variable does not have a significant impact on purchasing decisions. Meanwhile, Service Quality is proven to have a positive and significant impact as the dominant variable through a regression coefficient reaching 0.599 and a significance value of 0.000 (below 0.05). Simultaneously, Content Marketing, Product Quality, and Service Quality have a significant impact on Purchasing Decisions through the calculated F value reaching 45.502 and a significance of 0.000 below .05). The Adjusted R Square value of 0.584 indicates that 58.4% of the variation in Purchasing Decisions can be explained by these three variables, while the remaining 41.6% is influenced by other factors outside the research model. This finding confirms that strengthening content marketing strategies and improving service quality are key factors in driving consumer Purchasing Decisions.